Assessment of the levels of swimming skills development of the strongest swimmer teams at the I-XXXIV watersports championships from 1926-2018 - Ganchar, O.; Ganchar, I.; Ciorba, C.; Medynsky, S.; Arkhipov, A.; Chernyavskyi, O.; Cherkun, I. (Science, Movement & Health, 2021)
Relevance of the study. As a rule, the International Federation of European Swimming`s schedule - LEN, includes the European Watersports Championships. It has already been presented at the First European Swimming Championships since 1926. To date, 34 European Championships have been held, so it is very important to evaluate the achievements of the teams participating in the European continent to determine the real swimming development rate. Material. Average readings in the achievements of swimmers-winners have been summarized at 34 European water sports championships, respectively, at stages 1-2-3 among 127-525-906 men and 90-495-881 women at all distances in sports and marathon swimming programs over a long period of time from 1926 till 2018. The goal of research was to evaluate the team performance rating of among the participants of different gender from the European countries at different distances of sporting and marathoner swimming according to the prize medals they received during European Swimming Championship at stages I-II-III when they were conducted from 1926 till 2018. Results. The paper revealed an objective rating for the performance of the strongest swimmers teams based on the results of receiving both the number and quality of prize medals among men and women, at the I-XXXIV European Swimming Championships from 1926 to 2018 on stages I-II-III of their origin, development and further performance. At the first stage of the European Swimming (Aquatics) Championships, held from 1926 to 1950, the top ten most successful countries in terms of the level of the objective rating revealed, included: Germany-45 medals, the Netherlands-40, Hungary- 26, the United Kingdom-24, Sweden-20, France-18, Denmark-17, Italy-9, Belgium-5, Yugoslavia - 5 medals. In the second stage of the European Aquatics Championships, which took place from 1954 to 1991, the top ten most successful countries in terms of the level of the objective rating, included: GDR-287 medals, USSR-167, FRG-Germany-123+1* (marathon), the Netherlands-77+1*, Hungary-68+2*, the United Kingdom-66, Italy-45+4*, Sweden-45, France-30, Romania-17 medals. In the third stage of the European Aquatics Championships, held from 1993 to 2018, the top ten most successful countries for the results of the identified objective rating, included the following countries of the continent: Germany-177+42* (marathon) medals, Italy-158+37*, Russia-160+29*, France-132+16*, Hungary-138+9*, the United Kingdom-145+2*, Sweden-106, the Netherlands-84+21*, Ukraine-82+1*, Spain-61+7* medals.